1995
DOI: 10.18474/0749-8004-30.2.165
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pheromone Trap Design and Placement on Capture of Male Cydia caryana (Lepidoptera: Tortricidae: Olethreutinae) in Alabama Pecan Orchards and the Relationship of Trap Captures to Fruit Infestation

Abstract: The Pherocon Ic trap captured the greatest number of Cydia caryana (Fitch) adult males and all trap designs appeared to represent population trends equally well. Pooled data from all trap height experiments indicate that traps placed 9.14 m above the orchard floor captured significantly more adult males than those placed at 4.57 m height. Horizontal placement of traps within the tree canopy indicated a significantly greater capture in the central portion of the canopy than at other locations. Correlations betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1996
1996
1996
1996

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Similarly, Howell et al (1990) found that pheromone traps located 3.5 m high in sprayed apple trees caught more C. pomonella moths than those at 1.5 m 60% of the time, and pheromone traps placed 9 m above the ground in pecan orchards caught more adult males of hickory slmckworm, C. canjana (Fitch), than those placed 4.6 m high (McVay et al 1995). Our results in pheromone-treated orchards correspond with these findings, to the extent that more meaningful trap catch data arguably could have been gathered had our traps been located in the upper 3rd of the canopy during all 4 yr of our trials; however, our insight into the mating behavior of this species was not sufficient to prompt this change until the 1992 season.…”
mentioning
confidence: 93%
“…Similarly, Howell et al (1990) found that pheromone traps located 3.5 m high in sprayed apple trees caught more C. pomonella moths than those at 1.5 m 60% of the time, and pheromone traps placed 9 m above the ground in pecan orchards caught more adult males of hickory slmckworm, C. canjana (Fitch), than those placed 4.6 m high (McVay et al 1995). Our results in pheromone-treated orchards correspond with these findings, to the extent that more meaningful trap catch data arguably could have been gathered had our traps been located in the upper 3rd of the canopy during all 4 yr of our trials; however, our insight into the mating behavior of this species was not sufficient to prompt this change until the 1992 season.…”
mentioning
confidence: 93%